Penerapan Normalisasi Basis Data Pada Sistem E-Commerce Ratu Komputer - Jihan Bunga Firdaus; Ricky Bonardo; Izdihar Izzan Wibowo; Raihan Alma Putra; Medhanita Dewi Renanti (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
The operational success of Ratu Komputer's e-commerce depends heavily on the quality of the database structure used to manage transactions and customer information. Initial analysis shows that the raw data still contains redundancies, attributes that should be separated, and merging of information between entities that could potentially cause anomalies in the data storage and reading processes. This condition could further disrupt system performance as the number of transactions increases. This study aims to normalize the data structure through normalization stages to achieve Second Normal Form (2NF). The process involves identifying data requirements, relationships between entities, compiling data in UNF form, transforming it to 1NF by removing multivalue attributes, and improving it to 2NF to remove partial dependencies. The results of the study show that normalization is able to separate previously mixed entities, reduce data duplication, and produce a more structured table schema that meets the principles of referential integrity. The resulting 2NF schema is considered stable enough and can be used as a basis for the development of the Ratu Komputer e-commerce system in the next stage.